Chaplaincy in the outpatient setting-getting from here to there. Issue 2 (3rd April 2022) - Handzo, George; Hughes, Brian; Bowden, Jill; Kelly, Brian; Lynch, Jacqueline; Mercier, Michael; Pavlantos, Clio; Rothstein, Harry; Tuttle, Margaret
Abstract: One of the most evident trends in US health care and health care generally in the developed world is that more and more care is shifting to outpatient settings. This change opens up substantial opportunities, and in many cases, expectations for chaplains to extend the breadth of the care they provide in any health system. However, it also brings many challenges. This paper describes the journey of four very different inpatient chaplaincy services into the outpatient setting. These four examples focus on settings that would historically be thought of as outpatient—those that see patients within the brick and mortar of the health system.